Google Me : One-Click Democracy. - Cassin, Barbara (Meaning Systems Ser., 2017)
A witty, philosophically-informed, and openly polemical critique by Barbara Cassin of Google that looks at Google's claims to organize knowledge, and its alleged ethical basis. This critique goes to the heart of the assumed benefits to humanity of increasingly advanced internet technology.